Konsep Dakwah dan Dialog Progresif Eco Bhinneka Muhammadiyah melalui Kesadaran Lingkungan : The Concept of Eco Bhinneka Progressive Da'wah and Dialogue by Muhammadiyah through Environmental Awareness - Manalu, Musdodi (Direktorat Jenderal Bimbingan Masyarakat Islam, 2025)
This article examines the integration of environmental awareness in da'wah and interfaith dialogue through a case study of Eco-Bhinneka program by Muhammadiyah. In the midst of growing global concern for environmental issues, religious communities such as Muhammadiyah are responding with an inclusive da’wah approach and opening to interfaith collaboration. This program combines the mission of nature conservation with da'wah activity and interfaith dialogue. This study uses qualitative methods. This study uses the theories of Paul Swidler and Devaka Premawardhana. This study shows that Eco-Bhinneka program by Muhammadiyah became a collaborative space for caring for the environment while strengthening harmony. The result of this study shows that progressive interpretive approach to da'wah can produce an adaptive and contextual approach to ecological challenges.